Radio halo of NGC 4631: comparing observations and simulations. Issue 3 (29th January 2022) - Vijayan, Aditi; Dwarakanath, K S; Nath, Biman B; Kale, Ruta
ABSTRACT: We present low-frequency observations at 315 and 745 MHz of the edge-on, nearby galaxy NGC 4631 with upgraded Giant Metrewave Radio Telescope. We compare the observed surface brightness profiles along the minor axis of the galaxy with those obtained from hydrodynamical simulations of galactic outflows. These are 3D simulations that replicate star formation in a Milky-Way-sized galaxy and follow magnetized outflows emerging from the disc. We detect a plateau-like feature in the observed emission at a height of 2–3 kpc from the mid-plane of the galaxy, in qualitative agreement with that expected from simulations. This feature is believed to be due to the compression of magnetic fields behind the outer shocks of galactic outflows. We model the observed surface brightness profiles by assuming an exponential as well as a Gaussian fitting model. Using χ 2 statistics, we find that the exponential model fits the profiles better and we use it to determine the scale heights. We estimate the scale height for the synchrotron radio emission to be ∼1 kpc. The time-scales for advection due to outflows and diffusion of cosmic ray electrons are ≳5 and ∼160 Myr, respectively. Because advection acts on a time-scale much shorter than diffusion, we conclude that in NGC 4631 advection, rather than diffusion, plays the dominant role in the formation of radio halo. The spectral index image with regions of flatter radio spectral index in the halo appears to indicate possible effects of gas outflow from the plane of the galaxy.